Erythropoiesis Differences in Various Clinical Phases of Dengue Fever using Immature Reticulocyte Fraction Parameter - Amaylia Oehadian; Putri Vidyaniati; Jeffery Malachi Candra; Uun Sumardi; Evan Susandi; Bachti Alisjahbana (International Journal of Integrated Health Sciences, 2021)
Objective: To determine the mechanism of erythropoiesis that led to anemia using the Immature Reticulocyte Fraction (IRF) parameter in various clinical phases of dengue fever.Methods: This study was a comparative analytical research using secondary data derived from the Dengue-associated Endothelial Cell Dysfunction and Thrombocyte Activation (DECENT) research. The study was performed at Dr. Hasan Sadikin Hospital Bandung, Indonesia from March 2011 to March 2012. Patients were grouped into fever, critical, recovery, and convalescent phases and a healthy control was established. Data collected were analyzed using the Kolmogorov-Smirnov normality test, followed by Friedman test and Mann-Whitney post hoc test.Results: There were 244 subjects participating in this study. The median IRF for all subjects was 4.8% with an IQR of 2.4-8.1%. The values of Immature Reticulocyte Fraction in fever-phase, critical-phase, recovery-phase, convalescent-phase and healthy-control were 1.8% (IQR of 0.5-2.85%), 3.6% (IQR of 1.8-5.0%), 7.05% (IQR of 4.08-11.85%, 7.3 % (IQR of 3.95-9.3%) and 4.1% (IQR of 2.2-6.6%), respectively. There was a significant difference in IRF between groups (p<0.05).  The immature Reticulocyte Fraction in fever phase was significantly different from the IRF in other phases and healthy controls (p<0.05).Conclusions:There are changes in erythropoiesis activities detected through the IRF in various clinical phases of dengue infection. Erythropoiesis suppression occurs mainly during the fever phase and starts to be restored in the critical phase. In the recovery and convalescent phases, the erythropoiesis activities increase.  This is the first study describing IRF in multiple phases of dengue disease.